2008
DOI: 10.1161/strokeaha.108.523480
|View full text |Cite
|
Sign up to set email alerts
|

Ginkgo Biloba Extract Neuroprotective Action Is Dependent on Heme Oxygenase 1 in Ischemic Reperfusion Brain Injury

Abstract: Background and Purpose Ginkgo biloba extracts are now prescribed in several countries for their reported health benefits, particularly for medicinal properties in the brain. The standardized Ginkgo extract, EGb761, has been reported to protect neurons against oxidative stress, but the underlying mechanisms are not fully understood. Methods To characterize the oral consumption of EGb761 in transient ischemia, we performed the middle cerebral artery occlusion (MCAO) filament model in wild-type and heme oxygena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
87
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(91 citation statements)
references
References 26 publications
2
87
0
Order By: Relevance
“…53,54 Saleem et al showed that the standardised EGb761 significantly improved the outcome in mice after cerebral ischaemia and reperfusion in terms of neurobehavioral function and infarct size without affecting physiological parameters. 55 Our findings suggest a potential role of G. biloba in acute ischaemic stroke, and the findings are important in view of the fact that stroke is, at present, the third leading cause of death worldwide. 1 The mechanisms by which G. biloba normalise the cerebral damage, and reduce oxidative stress and inflammation, can probably be attributed to the antioxidant effects of flavonoids combined with the anti-inflammatory properties of the terpenoids bilobalide and ginkgolides A, B, C, M, J, and the terpenoids antagonists of platelet-activating factor (PAF), making this natural extract plausible to use in the treatment of ischaemic stroke, which is characterised by both oxidative damage and inflammation.…”
supporting
confidence: 51%
“…53,54 Saleem et al showed that the standardised EGb761 significantly improved the outcome in mice after cerebral ischaemia and reperfusion in terms of neurobehavioral function and infarct size without affecting physiological parameters. 55 Our findings suggest a potential role of G. biloba in acute ischaemic stroke, and the findings are important in view of the fact that stroke is, at present, the third leading cause of death worldwide. 1 The mechanisms by which G. biloba normalise the cerebral damage, and reduce oxidative stress and inflammation, can probably be attributed to the antioxidant effects of flavonoids combined with the anti-inflammatory properties of the terpenoids bilobalide and ginkgolides A, B, C, M, J, and the terpenoids antagonists of platelet-activating factor (PAF), making this natural extract plausible to use in the treatment of ischaemic stroke, which is characterised by both oxidative damage and inflammation.…”
supporting
confidence: 51%
“…In contrast, induction of HO-1 exerts potent protective effects in numerous preclinical disease models including sepsis, trauma, vascular proliferative disease, acute lung and liver injury, and cancer (1)(2)(3)(4)(5). A number of recent reports have demonstrated the benefits of HO-1 in the CNS, including the eye (6) and brain (7)(8)(9)(10)(11)(12). In the brain, expression of each HO isoform follows a distinct spatial and cell-specific distribution pattern.…”
Section: Introductionmentioning
confidence: 99%
“…We and others have unequivocally proven HO1 to be one of the prime targets of EGb 761-mediated protection, as observed in animal models of stroke and other conditions of oxidative stress (Chen et al, 2001; Zhuang et al, 2002; Saleem et al, 2008; Shah et al, 2011; Nada and Shah, 2012). EGb 761 enhances neurogenesis, and the crosstalk between HO1-induction and enhanced neurogenesis has only been recently discovered (Vanella et al, 2013; Nada et al, 2014).…”
mentioning
confidence: 71%